'Generation Nemo': motivations, satisfaction and career goals of marine biology students*. Issue 4 (2nd October 2018) - Lucrezi, Serena; Milanese, Martina; Danovaro, Roberto; Cerrano, Carlo
Abstract: Marine biology is an increasingly preferred study major and career among youth. This is particularly the case of countries with extensive coastlines, such as Italy. In order to understand what exactly is fuelling this trend, and whether it culminates in the successful absorption of marine biologists as valued workforce by society, this study investigated the motivations, satisfaction and career goals of marine biology undergraduate students in Italy. Although it was expected that scientific literacy in formal education plays an important role in motivating marine biology students, the results showed that intrinsic motivations and informal education play a more crucial role. The students consider realistic career options, although these imply having to leave the country. The results of this study were used to make recommendations on the importance of marine and ocean literacy in the formal educational system in Italy, and the general improvement of scientific literacy in formal school education. Recommendations were also made on the potential improvements that can be made by higher education institutions, to better equip marine biologists with the skills required by emerging sectors in society. Finally, considerations were made regarding the dimensioning of supply, offer and marketing of employment opportunities for marine biologists in Italy.